2021
DOI: 10.1038/s41598-021-96445-x
|View full text |Cite
|
Sign up to set email alerts
|

Relation between vitamin D deficiency and benign paroxysmal positional vertigo

Abstract: Benign paroxysmal positional vertigo (BPPV) is the most common cause of positional vertigo. Vitamin D deficiency may be one of the causes of its development. To assess the relation between recurrent attacks BPPV and Vitamin D deficiency. A case control study in which 40 patients were clinically diagnosed as posterior canal BPPV, Serum 25(OH) D was measured at 1st visit. Patients were divided into two groups; group A (20 patients) received Vitamin D supplementation in addition to canal repositioning maneuver an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
1
6
0
2
Order By: Relevance
“…Moreover, vaccination campaigns in Lebanon had not started yet during the study period. One possible explanation for the higher BPPV incidence rate in our study could be related to a high prevalence of vitamin D deficiency in the Lebanese population which has been associated with BPPV [ 17 , 18 ]. Emerging data suggests Vitamin D supplementation may reduce the risk of BPPV recurrence [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, vaccination campaigns in Lebanon had not started yet during the study period. One possible explanation for the higher BPPV incidence rate in our study could be related to a high prevalence of vitamin D deficiency in the Lebanese population which has been associated with BPPV [ 17 , 18 ]. Emerging data suggests Vitamin D supplementation may reduce the risk of BPPV recurrence [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors indicated that low levels of vitamin D were related to the development of BPPV and very low levels were associated with recurrence of this disease. Wu et al reported that a decreased 25(OH) vitamin D level in early-onset female patients may increase the odds of attacks of vertigo 1 week after successful repositioning maneuvers [ 37 ]. This study shows how important the role of vitamin D is in the treatment of BPPV, even after successful performance of the release maneuvers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that Yacovino method for the treatment of anterior semicircular canal BPPV has a recovery rate of 60.0% for the first manual reduction, and a recovery rate of 75.0% in one week (25). However, because the recurrence rate is significantly higher in the elderly, studies have shown that vitamin D and calcium supplementation can significantly reduce the recurrence rate of BPPV (43), and corresponding education should be carried out to reduce its potential incidence of falls.…”
Section: Reset Therapymentioning
confidence: 99%